2015
DOI: 10.1002/hed.23869
|View full text |Cite
|
Sign up to set email alerts
|

Improved overall survival and mortality in head and neck cancer with adjuvant concurrent chemoradiotherapy in national databases

Abstract: The literature shows mortality benefit of adjuvant CRT in patients with advanced head and neck cancer, reflected in SEER and NCDB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 52 publications
1
34
0
1
Order By: Relevance
“…Increased use of chemoradiation for patients with locally advanced HNC has improved local disease control and overall survival [1]. Unfortunately, chemoradiation is associated with increased acute and late effects that result in substantial symptom burden and decrements in quality of life (QOL) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Increased use of chemoradiation for patients with locally advanced HNC has improved local disease control and overall survival [1]. Unfortunately, chemoradiation is associated with increased acute and late effects that result in substantial symptom burden and decrements in quality of life (QOL) [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer associated with tobacco and alcohol usage is on the decline in developed Western countries, whereas there has been a significant increase in the incidence of oropharyngeal cancer associated with human papillomavirus (HPV) infection . Although the 5‐year survival rates for patients with head and neck cancer vary widely by tumor type and site, in the past 2 decades there have been significant improvements in oropharyngeal cancer survival rates and some improvement in survival in other head and neck cancer sites …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, 2 randomized trials demonstrated that chemoradiotherapy (CRT) for the high‐risk pathological features of positive surgical margins and/or extracapsular extension improved disease‐free survival and/or overall survival (OS) . Furthermore, a population‐based analysis from the National Cancer Database (NCDB) indicated that postoperative CRT improved the OS in patients with these high‐risk pathological features …”
Section: Introductionmentioning
confidence: 99%